HUBUNGAN PENGETAHUAN DAN SIKAP PASIEN TBC PARU DENGAN PERILAKU PEMERIKSAAN HIV DI PUSKESMAS PAMULANG KOTA TANGERANG SELATAN - AYUNINGTYAS, GITA; FITRIANI, DEWI; FITRIANI, DHIA DIANA; LESTARI, R TRI RAHAYUNING; HARDIANTI, TITA (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACT The HIV epidemic has shown its effect on increasing the TB epidemic throughout the world which has resulted in an increase in the number of TB cases in the community. In Indonesia, the prevalence of HIV in TB patients is around 2.4%. TB is also a challenge for controlling HIV/AIDS because it is the most common opportunistic infection (49%) in people living with HIV/AIDS (PLWHA). The purpose of this study was to determine the relationship between knowledge and attitudes towards HIV status examination at Pamulang Health Center, South Tangerang City. This study is a quantitative study with a cross sectional design. The sample size was 85 patients with pulmonary tuberculosis at the Pamulang Health Center. The data analysis used is univariate and bivariate analysis. Bivariate analysis using Chi Square test. The results of the univariate analysis showed that 55.29% had good knowledge of HIV testing, 27.76% had sufficient knowledge, and 12.94% lacked knowledge. Bivariate analysis with Chi square test with = 0.05 found that there was a relationship between knowledge and behavior of HIV examination in TB patients (pvalue = 0.01) and there was a relationship between attitudes of TB patients and behavior of HIV examination (pvalue = 0.00) OR = 2.310. The advice given is that the Puskesmas makes efforts to increase the knowledge of TB patients and establish cross-sectoral relationships in socializing TB and HIV. ABSTRAKEpidemi HIV menunjukan pengaruhnya terhadap peningkatan epidemi TBC di seluruh dunia yang berakibat pada meningkatnya jumlah kasus TBC di masyarakat. Di Indonesia prevalensi HIV pada pasien TBC adalah sekitar 2.4%. TBC juga merupakan tantangan bagi pengendalian HIV/AIDS karena merupakan infeksi oportunistik terbanyak (49%) pada orang dengan HIV/AIDS (ODHA). Tujuan, penelitian ini adalah mengetahui hubungan pengetahuan dan sikap terhadap pemeriksaan status HIV di Puskesmas Pamulang Kota Tangerang Selatan. Penelitian ini merupakan penelitian kuantitatif dengan desain cross sectional Jumlah sampel sebanyak 85 pasien TBC Paru di Puskesmas Pamulang. Analisis data yang digunakan adalah analisis univariat dan bivariat. Analisis bivariat menggunakan uji Chi Square. Hasil analisis univariat menunjukkan 55,29% memiliki pengetahuan baik terhadap pemeriksaan HIV, pengetahuan cukup 27.76%, dan pengetahuan kurang 12.94%. Analisis bivariat dengan uji Chi square dengan α=0.05 didapatkan ada hubungan antara pengetahuan dengan perilaku pemeriksaan HIV pada Pasien TB (pvalue=0.01) dan ada hubungan antara sikap pasien TBC dengan perilaku pemeriksaan HIV (pvalue=0.00) OR = 2.310. Saran yang diberikan adalah Puskesmas melakukan upaya untuk meningkatkan pengetahuan Pasien TBC serta menjalin hubungan lintas sektor dalam melakukan sosialisasi penyakit TBC dan HIV